A bibliometric analysis on the notion of sustainable business models and its relationship with the creation of territorial value for the environment - Mansri, Sara; Lahrach, Rahhal (Education and Development Research, 2025)
In a context where sustainability has become a central issue for companies and territories, this study aims to identify the importance of new sustainable business models (NBMS) and their interactions with territorial creation value. This study is one of the first to use bibliometric methods to describe and analyze the evolution of the literature published on the subject. The bibliometric analysis method was based on a 25-year study on a data set (1999-2024), collected by analyzing 115 articles via Zotero in a reliable way and randomly by analyzing 1,648 via Web Of Science. Using the VOSviewer software, the visualization of bibliometric data offers a glance at the articles, authors, journals, countries and fields that have the most effect on territorial value creation and the emergence of new sustainable business models. The analysis summarizes the most influential papers, authors, journals, and research topics. The results show the occurrence of three study themes: sustainable business models, territorial creating value, and innovation. In summary, this publication highlights the key findings of the study analysis and makes recommendations for future research areas in the subject.